Wyznaczanie gęstości naturalnej gleb = Determination of natural bulk density of soils - Wojtasik, Mieczysław; Szatten, Dawid Aleksander (Journal of Education, Health and Sport, 2015)
Wojtasik Mieczysław, Szatten Dawid. Wyznaczanie gęstości naturalnej gleb = Determination of natural bulk density of soils. Journal of Education, Health and Sport. 2015;5(3):218-228. ISSN 2391-8306. DOI: 10.5281/zenodo.16379 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A218-228 https://pbn.nauka.gov.pl/works/550075 http://dx.doi.org/10.5281/zenodo.16379 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. Wyznaczanie gęstości naturalnej gleb Determination of natural bulk density of soils Mieczysław Wojtasik, Dawid Szatten Instytut Geografii, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Streszczenie Najważniejszym wskaźnikiem stosunków wodnych i powietrznych gleb jest ich gęstość objętościowa. Wielkość tej cechy jest jednak bardzo zróżnicowana i zmienna w czasie. Dowiedziono, iż wśród zmiennych wielkości gęstości objętościowej istnieje taka, do której gleba dąży w procesach naturalnych ze stanu zagęszczenia lub spulchnienia. Tę charakterystyczną wielkość nazwano gęstością naturalną gleb (ρn) i opracowano metody jej wyznaczania. Słowa kluczowe: gęstość naturalna gleby, granulometryczny moduł gęstości naturalnej gleby, zawartość węgla organicznego, zawartość węglanu wapnia, głębokość w profilu. Abstract The most important indicator of water and air conditions of soils is their bulk density. The value of this characteristic is very diverse and variable in time. It has been proved that of the variables of bulk density of soil, is one to which soils tends in natural processes of the state of compaction or loosening. This characteristic size was called the natural bulk density of soils (ρn) and the method of its determination has been developed. Key words: natural bulk density of soil, granulometric index of natural soil bulk density, content of organic carbon, content of calcium carbonate, depth in profile.